Evaluation of healthcare waste management among health functionaries of Gujarat - Kuba, Ruchika; Joshi, Krupal; Kokare, Vikas; Singhal, Sanjay (Indian Journal of Community Health, 2023)
Introduction: Health Care Waste (HCW) is generated by various activities in healthcare facilities like hospitals, clinical, research institutions, laboratories, blood banks, etc. HCW is both infectious and hazardous and, unless rendered noninfectious and safe, can prove to be hazardous to people coming in contact with it. Objectives: To assess the Knowledge and Practice regarding HCW Management among health functionaries of districts of Gujarat and its association between the designation and qualification with the Knowledge and Practice score. Methodology: It was an observational and cross-sectional study using pretested, reliable, and valid questionnaire. A sample size of 152 was calculated based on the findings of a pilot study. We have implemented our study in Gujarat, divided into four parts (Saurashtra, Central, South, and North Gujarat). Study sites were selected equally in all four areas. Results: A total of 163 healthcare participants were involved in the study, most respondents were from primary healthcare centers (31.7%), followed by medical college hospitals (14.5%). In our study, Bhavnagar district had the highest number of contributors (21.7%), followed by Morbi district (19.1%). The hospital administrator category had the highest knowledge score, while Infection Control or Waste Management Officer had the highest practice score. MBBS/AYUSH graduates had the highest knowledge and practice scores. It is also apparent that staff nurses had better knowledge and practice scores than ANM. Conclusion: The overall assessment score was good for all health workers. Doctors' better knowledge and practice scores signify qualification's role in BMW management.